Vasculogenic Mimicry in Head and Neck Squamous Cell Carcinoma—Time to Take Notice - Salem, Abdelhakim; Salo, Tuula (Frontiers in Oral Health, 2021)
Head and neck squamous cell carcinoma (HNSCC) is a group of common cancers characterized by a swift growth pattern, early metastasis, and dismal 5-year survival rates. Despite the recent advances in cancer management, the multimodality approach is not effective in eradicating HNSCC. Moreover, the clinical response to the antiangiogenic therapy remains considerably limited in HNSCC patients, suggesting that tumor perfusion can take place through other non-angiogenic pathways. Tumor cell-induced angiogenesis is one of the main hallmarks of cancer. However, at the end of the previous millennium, a new paradigm of tumor cell-associated neovascularization has been reported in human melanoma cells. This new phenomenon, which was named “vasculogenic mimicry” or “vascular mimicry” (VM), describes the ability of aggressively growing tumor cells to form perfusable, matrix-rich, vessel-like networks in 3-dimensional matrices in vitro. Similar matrix-rich VM networks were also identified in tissue samples obtained from cancer patients. To date, myriad studies have reported intriguing features of VM in a wide variety of cancers including HNSCC. We aim in this mini-review to summarize the current evidence regarding the phenomenon of VM in HNSCC—from the available detection protocols and potentially involved mechanisms, to its prognostic value and the present limitations.